Pengembangan website interaktif PAI Studio: Inovasi media digital dalam pembelajaran sejarah kebudayaan islam bagi siswa sekolah dasar - Febrianti, Nur Wilujeng (Maliki Interdisciplinary Journal, 2025)
The problem of low student involvement in Islamic Religious Education (PAI) learning encourages the need for innovation in learning media that is interesting, contextual, and in accordance with the characteristics of 21st century students. This study aims to develop and test the effectiveness of digital learning media in the form of an interactive website called PAI Studio which contains Walisongo and Islamic boarding school materials. The study used a descriptive qualitative approach with a case study method and the Dick & Carey development model which was simplified into five stages: needs analysis, design, development, implementation, and evaluation. The implementation was carried out on five elementary school students at a TPQ in Malang City. The results of the observation showed an increase in student motivation to learn, focus, and participation during the learning process. The questionnaire response showed that 80% of students were happy and hoped that this media would be used again in the future. This media supports differentiated learning for students with visual and kinesthetic learning styles, and is able to create a learning atmosphere that is not rigid. Other advantages lie in the visual appearance, simple navigation, and integration of materials into fun activities. However, the limited number of digital devices and internet connections are obstacles to large-scale trials. Additional features such as interactive quizzes, audio narration, and offline versions are needed to make the media more inclusive and widely accessible. These findings indicate that the PAI Studio Interactive Website has the potential to be an applicable educational solution in technology-based PAI learning in elementary schools.